(untitled) (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: This study was to develop a controlled release formulation of various proton pump inhibitor drugs to maintain constant therapeutic levels of the drug over 24 h. Settings and Design: Dexlansoprazole was selected as model drugs. Various formulations were developed with different polymers for each drug molecule. To achieve pH-independent drug release of formu precompression blends of all formulations were subjected to various flow property tests, and all the formulations were passed the tests. Various grades of hydroxypropyl methylcellulose were employed as polymers. Statistical Analysis Used: Absence of probable chemical interactions of Fourier transform infrared between pure drug and polymers. Results: Dexlansoprazole dose was fixed as 30 mg. Total weight of the tablet was considered as 250 mg. Polymers were used in the concentration of 75 and 150 mg concentration. All the formulations were passed various physicochemical evaluation parameters and they were found to be within limits. Conclusions: Whereas from the dissolution studies it was evident that the formulation (F-2) showed better and desired drug release pattern, i.e. 98.79 Â± 0.48 in 24 h. It followed zero-order release kinetics mechanism.